The role of kisspeptin and its cognate receptor GPR54 in normal and abnormal placentation - Matjila, Mushi Johannes (Department of Obstetrics and Gynaecology, 2015)
Poor invasion of trophoblast cells in early pregnancy has been associated with preeclampsia and intrauterine growth restriction as well as other adverse pregnancy outcomes such as miscarriage, preterm birth and intrauterine death. Hypertensive disorders of pregnancy, including pre-eclampsia are one of the leading causes of maternal mortality in South Africa (Third report on Confidential Enquiries into Maternal Deaths in South Africa (2002-2004)) and the rest of the world. The currently accepted mechanism underlying the development of preeclampsia implicates poor trophoblast invasion and inadequate transformation of the maternal spiral arteries. Despite extensive research in this area, the control of trophoblast invasion and early placental development remains poorly understood. A whole host of factors such as oxygen tension, activation of matrix metalloproteinases (MMPs), angiogenic factors (VEGF-A) and immunological factors such as TNF alpha, interleukins and TGFβ have been shown to be involved in the control of trophoblast invasion. Our knowledge of the molecular details of pregnancy is unfortunately limited to in-vitro experiments and animal studies. Recently kisspeptins and their cognate receptor GPR-54 originally involved in tumour metastasis suppression and regulation of puberty, have been implicated in the inhibition of trophoblast invasion. Expression levels of kisspeptin and its receptor in trophoblast cells are highest in the first trimester, when control of trophoblast invasion is critical, and lower towards term.